Praxe domácího vzdělávání v rodině - Sterziková, Bibiana (Univerzita Karlova, Filozofická fakulta, 2022)
(in English): The Diploma thesis deals with the practice of an alternative form of individual education in a family institution. The aim of the work was to obtain information about family functioning if the obligation to educate at least one child at home is added to the normal duties of family life. The theoretical part deals with concepts that are closely related to this topic and which can describe home education in practice. The practical part describes a research survey that was conducted in four families. Interviews were conducted with parents-educators, and observations were made in families, along with insights into documents and materials that parents have at their disposal or that they created themselves to facilitate education. Thanks to these research methods, case studies have been created to present family life associated with home education. In conclusion, according to the information obtained, home education certainly affects the life of the family and the relationships between its individual members. Each family has its own system in home education, which shows its individuality. Thanks to this, children at home can grow up as unique personalities who will certainly be an enrichment for society. Keywords (in English): homeschooling, the pupil, teaching organization, family. (česky): Diplomová práce se zabývá praktikováním alternativní formy individuálního vzdělávání v instituci rodiny. Cílem práce bylo získat informace o rodinném fungování, pokud se k běžným povinnostem rodinného života přidá povinnost vzdělávat alespoň jedno dítě doma. V teoretické části jsou rozebrány pojmy, které s tímto tématem úzce souvisí a které mohou přiblížit, jak domácí vzdělávání v praxi probíhá. V praktické části je popsáno výzkumné šetření, které bylo uskutečněno ve čtyřech rodinách. S rodiči - vzdělavateli byly provedeny rozhovory, v rodinách bylo uskutečněno pozorování spolu s nahlédnutím do dokumentů a materiálů, které mají rodiče k dispozici, či které si sami vytvořili pro usnadnění vzdělávání. Díky těmto ...